Performance Evaluation of Sprinkler Irrigation System in a Rural Watershed - R. K. Sharma; K. K. Nathan; Ashok Kumar; H. R. Singh; Khushi Ram (Journal of Soil and Water Conservation, 2022)
Over-exploitation of groundwater through excessive pumping in irrigation sector results in the fast depletion of this water resource in the country. Declining water-table levels in highly potential and productive regions have raised concern on hydrological sustainability of intensive irrigated cropping system, which is the back-bone of India’s food grain production. Under such a scenario, it is increasingly being felt that the country must frame a long-term policy of conservation, management and sustainable utilization of water resources to address the newly emerging challenges in the sector. The long-term policy needs to focus on the introduction of efficient water utilization systems and increased water use efficiency of the existing ones. Though efforts are being made to introduce highly efficient irrigation methods in rural areas, no attempt is being made to develop guidelines for their efficient operations in view of practical constraints in these areas. As a result, these efficient systems perform much below their potential efficiency in rural areas. The present study was conducted in the Shikohpur village watershed to evaluate the performance of sprinkler irrigation system in view of the practical constraints faced by the farmers. The performance of the sprinkler system was found very poor with its adverse impact on water-table level decline in the watershed. Unsatisfactory performance of the sprinkler system has been attributed to the lack of technical know-how amongst the farmers, payment of power tariff on monthly basis and the erratic power supply in the area.